Kewenangan dan Sinergi Lembaga Pelaksana Hukum Jinayah dalam Penegakan Syariat Islam di Aceh - Deden Najmudin; Irwan Sunardi; Krisna Aulia; M.Rassya Al-ghifari (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This research is motivated by the gap between the normative provisions and the empirical practice of the authority of the Wilayatul Hisbah (WH) in enforcing criminal law in Aceh. Normatively, the WH is positioned as an implementing institution of Islamic Sharia that has legal legitimacy in the supervision, guidance, and initial action against violations of the qanun jinayah. However, in practice, the limited authority of the WH, especially in the investigation aspect, gives rise to coordination problems and structural dependencies with the Police and the Prosecutor’s Office, so that synergy between criminal law enforcement institutions has not been running optimally. This study aims to analyze the authority of the Wilayatul Hisbah and its synergy patterns in the Islamic Sharia enforcement system in Aceh, with a focus on the conformity between the normative legal framework and its implementation. The method used is normative legal research with a statutory and conceptual approach, through a literature study of laws and regulations, Aceh qanun, legal literature, and relevant previous research results. Data analysis was conducted qualitatively with deductive-analytical reasoning. This study uses the theory of authority and the concept of the criminal justice system for criminal law as an analytical framework. The research findings indicate that the Wilayatul Hisbah (Islamic Jurisdictional Authority) has a strong legal basis, but functionally, it is unable to optimally fulfill its role due to the lack of comprehensive technical regulations regarding the limits of authority and synergy mechanisms between institutions. The novelty of this research lies in its integrative analysis, which positions the Wilayatul Hisbah as a crucial component of the criminal justice system, requiring structural strengthening and institutional coordination. This research is expected to provide conceptual and practical contributions to the development of more effective, coordinated, and equitable Islamic Sharia enforcement policies in Aceh.